ChemInform Abstract: Bare Magnetic Nanoparticles: Sustainable Synthesis and Applications in Catalytic Organic Transformations. Issue 50 (16th December 2014) - Hudson, Reuben; Feng, Yuting; Varma, Rajender S.; Moores, Audrey
Abstract Review: 153 refs.